The Opposing Role of Propionate in Modulating Listeria monocytogenes Intracellular Infections - Hobbs, Laura; Allen, Leah; Bias, Megan; Johnson, Stephanie; DeRespiris, Hannah; Diallo, Chantal; Bui, Loan; Sun, Yvonne (Frontiers in Microbiology, 2021)
Listeria monocytogenes is a Gram-positive, intracellular pathogen responsible for the highly fatal foodborne illness listeriosis. Establishing intracellular infections requires the coordinated expressions of a variety of virulence factors, such as the pore-forming toxin listeriolysin O (LLO), in response to various intra- and extracellular signals. For example, we previously reported that L. monocytogenes differentially modulated LLO production in response to exogenous propionate, a short chain fatty acid either used in salt form as a human food ingredient or produced endogenously by gut microbial fermentation. Therefore, propionate is likely a continuously present signal throughout the L. monocytogenes transmission and infection process. However, little is known about the role of propionate in modulating L. monocytogenes-host interactions. Here we investigated the impact of propionate treatment on L. monocytogenes intracellular infections using cell culture infection models. Propionate treatment was performed separately on L. monocytogenes or host cells before or during infections to better distinguish pathogen-versus-host responses to propionate. Intracellular CFU in RAW264.7 macrophages and plaque diameters in L-fibroblasts were measured as proxy for intracellular infection outcomes. Nitrite levels and cellular morphology were also measured to assess host responses to propionate. We found that propionate pretreatment of anaerobic, but not aerobic, L. monocytogenes significantly enhanced subsequent intracellular infections in both cell types and nitrite production by infected macrophages. Propionate treatment of uninfected macrophages significantly altered cell morphology, seen by longer cells and greater migration, and reduced nitrite concentration in activated macrophages. Treatment of macrophages with propionate prior to or during infections significantly inhibited intracellular growth of L. monocytogenes, including those pre-treated with propionate. These results showcased an opposing effect of propionate on L. monocytogenes intracellular infections and strongly support propionate as an important signaling molecule for both the pathogen and the host cell that can potentially alter the outcome of L. monocytogenes-host interactions.